1980
DOI: 10.1038/ki.1980.20
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of carbonic anhydrase in the rat kidney

Abstract: The rat kidney was studied by light and electron microscope after it was histochemically stained for carbonic anhydrase activity. Glomeruli and Bowman's capsule were inactive. Convoluted proximal tubules showed intense activity at the brush border and the basolateral membranes. Cytoplasmic activity also was found. Straight proximal tubules had considerable enzyme activity at basolateral membranes but only low activity at the brush border and in the cytoplasm. In nephrons with long loops, the descending thin li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 25 publications
7
59
0
Order By: Relevance
“…CA activity has been identified in basolateral membranes, in addition to renal luminal membranes, by biochemical (McKinley and Whitney 1976;Wistrand and Kinne 1977;Brechue et al 1991) and histochemical (Lönnerholm and Ridderstråle 1980;Dobyan et al 1982;Lönnerholm and Wistrand 1984;Ridderstråle et al 1992) methods. IHC studies have revealed CA IV in basolateral membranes of proximal tubules of rat and rabbit kidney (Brown et al 1990;Schwartz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA activity has been identified in basolateral membranes, in addition to renal luminal membranes, by biochemical (McKinley and Whitney 1976;Wistrand and Kinne 1977;Brechue et al 1991) and histochemical (Lönnerholm and Ridderstråle 1980;Dobyan et al 1982;Lönnerholm and Wistrand 1984;Ridderstråle et al 1992) methods. IHC studies have revealed CA IV in basolateral membranes of proximal tubules of rat and rabbit kidney (Brown et al 1990;Schwartz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical studies in mouse and rat kidney have demonstrated membrane-associated CA activity in distal tubule and intercalated cells of the collecting ducts, suggesting that these tubule segments express thus far unidentified membrane-associated CA isoenzymes (Lönnerholm and Ridderstråle 1980;Dobyan et al 1982;Ridderstråle et al 1992). To compare the localization of CA XII with CA IV and XIV along the mouse and rat nephron and with the localization of CA XII in human kidney, we raised specific polyclonal antibodies to recombinant mouse CA XII.…”
mentioning
confidence: 99%
“…The superficial distal tubule is lined by several cells types (15,(38)(39)(40)(41). In analogy to observations made on the cortical collecting duct, some cells in the initial collecting tubule ("late distal tubule") may have the ability to secrete bicarbonate ions into the tubular lumen (10).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, both the medullary (MTAL) and cortical (CTAL) segments of the rat TAL absorb bicarbonate at relatively high rates (3). This TAL ability requires carbonic anhydrase activity (4) and, indeed, rat TAL cells (5), like human TAL cells (6), are rich in carbonic anhydrase. In addition, the TAL is a site of regulation of the renal acid-base handling in that chronic metabolic acidosis and increased sodium intake are associated with adaptive increases in the ability of the rat MTAL to absorb bicarbonate (7).…”
Section: Introductionmentioning
confidence: 99%